Analysis of digital marketing strategies used by micro and small businesses during and after the pandemic period (Research, Society and Development, 2025)
Micro and small businesses overcome several challenges in the contemporary market, one of the allies for overcoming said challenges is digital marketing. This article looked at the digital marketing strategies used by micro and small businesses during and after the pandemic period. The COVID-19 pandemic has boosted the use of digital platforms, such as social media, e-commerce and content marketing, standing out as an essential tool for business survival in a period of crisis. To achieve the objective of analyzing the digital marketing strategies used by micro and small companies during and after the pandemic period, a qualitative approach was used, through exploratory and descriptive methods. In view of this, it was possible to identify some strategies and benefits of digital marketing, including maintaining relationships with customers and expanding digital presence, as well as challenges, such as limited financial resources and lack of technical training. In the post-pandemic period, digital strategies have developed a relevant role, reinforcing the importance of digital marketing as an indispensable component for the sustainable growth of micro and small businesses.